¿Es necesaria una lista de verificación de seguridad para el parto vaginal? - amírez Cabrera, Juan Orestes R (2024)
Introduction: Vaginal to delivery care is a complex, multidisciplinary process thatrequires institutions that provide safe and efficient surveillance of pregnant women.In obstetric practice, the physician frequently makes critical decisions in a short periodof time and adverse events may occur. Within the framework of the WHO WorldAlliance for Patient Safety whose aim is to reduce risks during the delivery process,the use of safety checklists has been promoted as a strategy to reduce maternaland neonatal death. Objective: To elaborate a Vaginal Birth Safety Checklist (VBSC)to be applied to all pregnant women admitted to San Bartolomé hospital for herdelivery care. Methodology: To design a correct sequence of procedures and usefulactions to improve the safety of the pregnant woman during her stay, including theperiods of dilatation, expulsion and immediate puerperium, using a questionnaireaddressed to the different members of the health team involved in the care of boththe mother and the newborn. Some questions to the patient are also included.Results: Systematized care is achieved, communication between the care team andthe patient is improved, decision-making is favored, risks are identified, and deliverycare is standardized. Conclusion: The VBSC is a valuable tool for optimizing safetyand quality in vaginal delivery care, the success of which will depend on how it isintegrated into clinical practice.